Эмма из Прованса - Гришина Вера Николаевна (Серия "Аллея", 2023)
Экземпляры: ЦБ (20230529) / Инвентарный номер: 59784 / Цена: 442.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Г 85 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44